Gestational Age-Specific Markers Associated with Postnatal Intervention in Fetal Suspicion of Coarctation of the Aorta - Amar, Sam; Moore, Shiran S.; Wutthigate, Punnanee; Ohayon, Amanda; Martinez, Daniela V.; Simoneau, Jessica; Renaud, Claudia; Altit, Gabriel (American Journal of Perinatology, 2024)
Objective Fetal diagnosis of coarctation of the aorta (CoA) is currently associated with a high false-positive rate. Many predictive markers may be gestational age (GA)-specific. We sought to establish GA-specific traditional and speckle-tracking fetal echocardiography (STE) markers predictive of true CoA in neonates with prenatal suspicion.Study Design This is a retrospective case–control study. We compared the fetal ventricular and arch dimensions, as well as the deformation parameters by STE, of infants who required a postnatal intervention for their CoA with those who did not. Cohort was stratified based on GA before or after 30 weeks. Data extractors were masked to the outcome. The first fetal echocardiogram available was used.Results Seventy-five newborns with a fetal echocardiography performed between October 2013 and May 2022 for an antenatal suspicion of CoA were included, of which 59 (79%) had an aortic arch with nonsignificant obstruction upon ductal closure, and 16 (21%) underwent a neonatal intervention for a confirmed CoA. Before 30 weeks' GA, the right ventricular to left ventricular (RV/LV) end-diastolic width and end-diastolic area (EDA) ratios were most associated with postnatal CoA confirmation (area under the curve [AUCs] = 0.96 and 0.92). After 30 weeks' GA, the RV/LV end-diastolic width ratio (AUC = 0.95), the Z-score for the ascending aorta (AUC = 0.93), and the LV end-diastolic width Z-score (AUC = 0.91) performed the best. A decreased RV peak longitudinal strain was observed in those who developed true CoA and performed well by receiver operating characteristic analysis after 30 weeks (AUC = 0.85). In the overall cohort, the RV/LV EDA ratio was the most sensitive predictor of CoA and identified all cases with CoA. Indeed, a cutoff > 1.24 had a specificity of 69.5% and a sensitivity of 100% (receiver operating characteristic curve with an AUC of 0.88).Conclusion We outlined sensitive and specific fetal markers associated with postnatal CoA based on GA at suspicion.Key Points
Keywords: coarctation of the aorta; fetal echocardiography; STE; strain; congenital heart defect; ventricular disproportion